An Archaeological Perspective on Neocolonialism, Heritage-Making, and Historical Preservation at the Henry Whitfield House in Guilford, Connecticut - Farley, William; Mcbride, Michael; Chesler, Kevin; Godfrey, Jonathan; Pascale, Devin (Bulletin of the Archaeological Society of Connecticut, 2020)
Southern Connecticut State University conducted its first year of excavations at the Henry Whitfield State Museum in Guilford, Connecticut in July, 2018. This research was a continuation of nearly fifty years of intermittent archaeological research at the Whitfield Museum property. The 2018 field season was spent exploring a previously uninvestigated locus. While we did find some evidence of 17th, 18th, and 19th century activities at this locus, the most exciting finds were related to the neocolonial revival of the museum property in the first half of the 20th century. In addition to a general report on findings from the 2018 excavations, we explore the historical context of the Whitfield House in the late 19th and early 20th centuries, especially its perceived emblematic association with colonial English descendant communities in light of the period’s social anxieties about immigration, shifting racial dynamics, and economic and religious change.
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Paleoenvironments of Gona, Ethiopia, between 3-1 Mya: Evidence from faunal analysis - Leiss, Amanda C.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2020)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Review of" Indigenous Persistence in the Colonized Americas: Material & Documentary Perspectives on Entanglement" - Farley, William A. (Historical Archaeology, 2020)
Keywords: book.review; dept.ant; peer-reviewed

Language, labor and reification - McGill, Kenneth (Language Sciences, 2020)
In this article, I attempt to describe how language is reified, using the call center as an extended example. I take up recent debates regarding language and economic value, attempting to disentangle a by now substantial series of arguments about language and commodification. The theoretical core of the paper is drawn from the work of Georg Lukács, who provided the account of reification that was at the root of twentieth century critical theory. Following Lukács, I argue that what is indispensable in the process of reification is both a “contemplative stance” in relation to economic laws and the presence of “special partial systems” within the production process of commodities. These are particularly important considerations for what I refer to as the one-sided rationalization of language that occurs in call centers in particular, but also on a more widespread social basis. © 2020 Elsevier Ltd
Keywords: Commodity; Consciousness; Economic value; Language; Reification; dept.ant; peer-reviewed

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Paleoenvironmental changes during the last 6 million years at Gona, Afar Region, Ethiopia - Levin, Naomi E; Simpson, S.; Rogers, Michael J.; Semaw, S. (African Paleoecology and Human Evolution, 2020)
Keywords: dept.ant

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull

The bioarchaeology of Wari collapse in Cuzco, Peru: A study of health and trauma from the Middle Horizon-Late Intermediate Period transition at Cotocotuyoc - Andrushko, Valerie (The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, 2020)
Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, Peru analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500–1000) and resulted in the rise of the Inca state. The contributors to this collection present evidence of the Wari civilization’s robust, imperialistic occupation of Cuzco, and argue that this presence laid the groundwork for later regional polities that can be traced to the Late Horizon Inca period (AD 1476–1532). This collection fills a gap in scholarly literature on Cuzco prehistory, the provincial southern highlands of the Wari civilization, and early imperialism in the Andes.
Keywords: dept.ant